ANALISIS SISTEM PEMBUKTIAN TERBALIK DALAM TINDAK PIDANA PENCUCIAN UANG - Nurdin, Nurdin (Katalogis, 2015)
Analysis of Shifting Burden of Proof System in Money Laundering by Nurdin. The research question was whether or not the shifting burden of proof system in money laundering had been consistent with the principle of Presumption of Innocence in civil law of procedures. The objective of the research was to identify whether or not the application of shifting burden of proof system in money laundering had been consistent with the prinsiple of Presumption of Innocence in civil law of procedures. The adopted research method was juridical normative. The results of the research suggested that the shifting burden of proof system did not conflict with the principle of presumption of innocence as implementation of human rights as it was naturally limited and balanced. The shifting burden of proof was limitedly applied in court proceeding and the issue evidenced by the defendant only concerned with his properties related with the civil case. On the other hand, the prosecutor remained to prove his accusation. The shifting burden of prood consistently respected the proportional balance between individual freedom protection and individual rights seizure in connection with his properties alleged to have been acquired unlawfully.